High complexity nursing in pressure injury prevention: An integrative literature review - Correa, ígatha de Oliveira; Nocelli, Laura Teixeira; Santos, Luísa Itaborahy; Fernandes, Maria Eduarda Lage; Damasceno, Mikaella Silva; Rocha, Thiago Casali (Revista Feridas, 2019)
ntroduction: To verify, through an integrative review, the techniques of prevention of pressure injuries (PI) in patients hospitalized in the intensive care unit (ICU). The aim of the present study was to analyze different ways of preventing pressure injuries in complex patients, as a way to promote the increase of quality of life. Methods: Studies published between 2014 and 2019 were analyzed, based on the Medline database through Pubmed, and the MeSH was used to construct the search phrase. The following inclusion criteria were established: randomized controlled trials (RCT) conducted in humans, in English and available in full. As exclusion criteria: studies performed outside the hospital environment. The following variables were used to select studies: time of treatment, outcome of intervention, and risk of developing pressure ulcers in ICU patients. Results: A total of 359 studies involving the prevention of PI were identified. However, from the application of the defined criteria, only 25 studies fell within the scope of this review. Of these, only three were chosen. Conclusion: This review shows the effects of preventing PIs in critically ill hospitalized patients. However, the use of turning every 2 hours has less significance in the scientific community. In addition, technological advances as a form of prevention for PIs have shown greater resolution in complex patients. However, it is necessary that more studies be carried out in other hospital units using these instruments to deepen the theme and to ensure their effectiveness.